(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The aim of this study was to determine if there is a connection between the inquiry-based teaching of science in primary school and the development of the students’ learning to learn competence. The research shows that through inquiry-based teaching students developed a higher level of the learning to learn competence than by using traditional teaching methods. Therefore, it is recommended to use inquiry-based learning as often as possible, because by developing the students’ learning to learn competence, students will be empowered for the process of lifelong learning.